Strategi Pembelajaran Oleh Guru dalam Meningkatkan Efektifitas Belajar Siswa Kelas X pada Mata Pelajaran Geografi di SMAN 6 Malang - Yohanes Donia Muda; Yuli Ifana Sari (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study was motivated by the fact that teachers' learning strategies are very important for improving student motivation, understanding, and learning effectiveness. The purpose of this study was to identify the learning approaches used by teachers, the challenges faced, and how these approaches were applied to students in the 10th grade Geography class at SMAN 6 Malang. This study uses a descriptive qualitative methodology that collects data through interviews, observations, and documentation. Furthermore, the data were analyzed through the steps of reduction, presentation, and conclusion drawing. The research information consisted of geography teachers, 10th grade students, and other related parties. The results showed that expository and inquiry strategies were the most effective learning strategies used by teachers to help students learn. Unresponsive students, negative peer influence, and the habit of sleeping in class are some of the obstacles in the learning process. Students' ability to systematically and coherently organize and convey conclusions demonstrates the impact of applying learning strategies. According to this study, teachers must continue to improve their skills through learning training. Students are also expected to be more focused and active during the teaching and learning process.